SCM-198 Prevents Endometriosis by Reversing Low Autophagy of Endometrial Stromal Cell via Balancing ERα and PR Signals - Lin, Yi-Kong; Li, Yun-Yun; Li, Yue; Li, Da-Jin; Wang, Xiao-Lin; Wang, Li; Yu, Min; Zhu, Yi-Zhun; Cheng, Jia-Jing; Du, Mei-Rong (Frontiers in Endocrinology, 2022)
Background: Endometriosis (EMS), an endocrine-related inflammatory disease, is characterized by the imbalance of estrogen and progesterone in ectopic lesions. However, its pathogenic mechanism has not been fully explored. While SCM-198 is the synthetic form of leonurine with multiple pharmacological activities, such as anti-oxidation and anti-inflammation, whether it could inhibit the progress of EMS by regulating estrogen signaling and inflammation remains unknown. Methods: The therapeutic effects of SCM-198 on EMS and its potential mechanism were analyzed by establishing EMS mouse models and performing RNA-seq assay. ELISA was performed to detect estrogen and TNF-α concentration in normal endometrial stromal cells (nESCs) and ectopic endometrial stromal cells (eESCs), with or without SCM-198 treatment. Western blotting, RNA silencing and plasmid overexpression were utilized to analyze the relationship among inflammation, endocrine and autophagy as well as the regulation of SCM-198 on the inflammation-endocrine-autophagy axis. Results: Increased estrogen-ERα signaling and decreased PRB expression co-led to the hypo-autophagy state in eESCs, which further inhibited the apoptosis of eESCs. The high expression of TNF-α in eESCs enhanced the anti-apoptosis effect mediated by low-autophagy through activating aromatase-estrogen-ERα signaling pathway. SCM-198 inhibited the growth of ectopic lesions in EMS mice and promoted the apoptosis of eESCs both in vivo and in vitro. The apoptosis effect of SCM-198 on eESCs was realized by upregulating the autophagy level via inhibiting TNF-α activated aromatase-estrogen-ERα signal and increasing PRB expression. Conclusion: Inflammation facilitated the progress of EMS by disrupting estrogen regulatory axis. SCM-198 restrained the growth of EMS by regulating the inflammation-endocrine-autophagy axis.